Emotion recognition accuracy only weakly predicts empathic accuracy in a standard paradigm and in real life interactions - Flykt, Anders; Dewari, Asrin; Fallhagen, Martin; Molin, Anders; Odda, August; Ring, Joel; Hess, Ursula (Frontiers in Psychology, 2023)
The relationship between decoding ability (Emotion recognition accuracy, ERA) for negative and positive emotion expressions from only video, only audio and audio-video stimuli and the skill to understand peoples’ unspoken thoughts and feelings (Empathic accuracy, EA) was tested. Participants (N = 101) from three groups (helping professionals with and without therapy training as well as non-helping professionals) saw or heard recordings of narrations of a negative event by four different persons. Based on either audio-video or audio-only recordings, the participants indicated for given time points what they thought the narrator was feeling and thinking while speaking about the event. A Bayesian regression model regressing group and ERA scores on EA scores was showing weak support only for the EA scores for ratings of unspoken feelings from audio only recordings. In a subsample, the quality of self-experienced social interactions in everyday life was assessed with a diary. The analysis of ERA and EA scores in relation to diary scores did not indicate much correspondence. The results are discussed in terms of relations between skills in decoding emotions using different test paradigms and contextual factors.